1, 3, 4-Oxadiazole derivatives as potential antitumor agents: discovery, optimization and biological activity valuation. Issue 2 (2nd December 2015) - Luo, Yin; Liu, Zhi-Jun; Chen, Guo; Shi, Jing; Li, Jing-Ran; Zhu, Hai-Liang
Abstract : New 1, 3, 4-oxadiazole derivatives have been synthesized and evaluated for their FAK inhibitory activity and anticancer activity. The most active compound5h was studied by docking simulation to explore the binding model. Abstract : Recent studies have proved that focal adhesion kinase (FAK) is a new potential therapeutic target in cancer therapy. In this study, a virtual screening was conducted to discover potential candidates for FAK inhibitors. Based on the results, a series of novel oxadiazole derivatives (5a–5q ) bearing the benzotriazole group were designed and synthesized for FAK inhibitory evaluation. Among the compounds, 5h, which has an ortho methoxy group on the benzene ring, exhibited the most potent inhibitory activity for cancer cell growth with an IC50 value of 11 μM and 0.250 μM against Hela cells and FAK, respectively. Further, the apoptosis assay indicated that compound5h induced the apoptosis of HeLa cells, and docking simulation showed that5h could bind to the FAK protein catalytic region. Taking these together, 5h could be a lead for discovering novel FAK inhibitors.